Predictive immunonutritional biomarkers for the severity and recovery of sudden sensorineural hearing loss: a prospective clinical study - Zhang, Xu; Guo, Weixun; Guan, Bing; Yang, Chunping (Frontiers in Neurology, 2025)
BackgroundSystemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) are known to predict the severity and prognosis of various diseases. However, their role in sudden sensorineural hearing loss (SSNHL) is unclear.MethodsThis study collected 100 patients with SSNHL and 100 healthy volunteers. According to the severity, type, prognosis and SII and PNI levels of SSNHL, we used the Spearman linear correlation method to conduct correlation analysis. At the same time, we constructed logistic regression analysis to explore the predictive value of PNI and SII on the prognosis of SSNHL patients, and used ROC curves to verify the prognostic model. Cohen’s d values were calculated for select significantly different parameters to assess effect sizes.ResultsCompared with control group, PNI levels were significantly lowered in SSNHL patients, while SII levels were significantly higher. And a significant correlation was observed between the two variables (R = -0.437, p < 0.001). At the same time, compared with patients with mild and moderate SSNHL, patients with severe SSNHL had the lowest PNI levels and the highest SII levels. PNI showed a negative correlation with hearing loss severity once the proper categorization of severity was taken into account, whereas SII was positively correlated with severity. After adjusting for potential confounders, both high SII and low PNI were independently associated with worse prognosis in SSNHL. Effect size analysis (Cohen’s d) revealed moderate practical significance in the differences in PNI levels between groups.ConclusionIn patients with SSNHL, PNI levels were significantly lowered, while SII levels were significantly higher. Furthermore, a negative correlation was observed between these two indicators. A negative correlation between PNI and SSNHL severity and a positive correlation between SII and severity were observed. These findings suggest that PNI and SII could serve as potential biomarkers for predicting SSNHL prognosis.